Mathematical Modelling of Radiating Processes in the Solids Irradiated by Heavy Ions (ҚазҰУ Хабаршысы. Математика, механика, информатика сериясы, 2018)
In this work the modelling of the processes of radiation defect formation in solidsirradiated by heavy ions within the cascade-probabilistic method (CPM), which is analytic. All themathematical models describing these processes are received both from physical reasons, and fromKolmogorov-Chapman equations. Essence of CPM consists in reception and further use cascadeprobabilisticfunctions (CPF), CPF makes sense of the fact that the particle generated on depth ℎ′will reach depth h after N number of impacts.Mathematical models are received in such a way thatin them are considered energy losses to ionization and excitation of the electron envelopes of theatoms of medium with interaction of heavy ions with solid
Keywords: modeling; defect formation; cascade-probabilistic; ion; target; recurrence relation; approximation; concentration; vacancies cluster; spectrum of primarily knocked-on atoms